Parasitism and horn quality in male Spanish ibex (Capra pyrenaica hispanica) from Andalucia based on coprological analysis and muscle biopsy - Luzon, M.=700 1 Santiago Moreno, J.; Meana, A.; Toledano Diaz, A.; Pulido Pastor, A.; Gomez brunet, A.; Lopez Sebastian, A.
(Es, En)
Ilus., 29 ref.
Keywords: CABRA MONTES; ANALISIS HISTOCITOLOGICO; MUSCULOS; CALIDAD; CUERNOS; PARASITISMO; ENFERMEDADES DEL SISTEMA DIGESTIVO; BRONQUIOS; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH